The Indo-Pacific economic framework: can the US pull it off? - Pitakdumrongkit, Kaewkamol (2022)
The US-led Indo-Pacific Economic Framework for Prosperity (IPEF) has been launched. It seems well-received by several regional economies. Nevertheless, the IPEF will face several challenges, triggering questions of whether and how the US will be able to advance it. Three member states of ASEAN have not been included, and there is no collective ASEAN position on it.